REVIEW OF ISLAMIC ECONOMIC LAW ON TRADERS 'INTERNET DATA SELLING PRACTICES IN GAMPONG KOPELMA KECAMATAN SYIAH KUALA BANDA ACEH - Suhaimy Syahrul; Muhammad Yusran Hadi; Gamal Achyar (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2020)
This research was conducted based on the form of fraud and the obscurity of business actors, which, if allowed to continue, will further harm consumers. In fact, consumers have not received maximum service, so consumers are always ignored by the behavior of business actors who commit fraud, just because they want to get a profit. The research objective in this thesis is to find out how to review Islamic economic law on the practice of buying and selling internet data package pulses for traders in Gampong Kopelma, Syiah Kuala District, Banda Aceh. This research uses qualitative research with descriptive analysis method. And data obtained from interviews. The results of this study indicate that in the practice of buying and selling the active period of internet data packages at the Kopelma Village Counter, Syiah Kuala District, Banda Aceh, buyers come directly to the place. In that place the buyer can choose the data package to be used and purchased. Prices and products also vary, depending on the data package and the amount of quota, as well as the active period for how many months. The products sold include Simpati, XL, Axis, Tri, Indosat, Smartfren and other products. After finding the internet data package that you want to use, the buyer begins the transaction. The law of buying and selling internet data pulses by traders in the Kopelma Darussalam area is legal and is in accordance with the terms and conditions of buying and selling. However, there are some sellers who do not convey the correct information, resulting in losses for the buyer such as the active period or the validity period of the package which is shorter than the time that has been delivered.